Intestinal obstruction caused by disseminated mycobacterium avium complex disease following solid organ transplantation: a case report - Akane Mita; Sho Nakakubo; Yusuke Nishimura; Hideki Shima; Masaaki Watanabe; Tsuyoshi Shimamura; Satoshi Konno (BMC Infectious Diseases)
Abstract Background Mycobacterium avium complex (MAC) is a common pathogen causing non-tuberculous mycobacterial infections, primarily affecting the lungs. Disseminated MAC disease occurs mainly in immunocompromised individuals, such as those with acquired immunodeficiency syndrome, hematological malignancies, or those positive for anti-interferon-γ antibodies. However, its occurrence in solid organ transplant recipients is uncommon. Herein, we report a rare case of disseminated MAC disease following liver transplantation, which led to an obstructive mass in the intestinal tract that required differentiation from a malignant tumor. Case presentation A 76-year-old woman, who had undergone living-donor liver transplantation 15 years earlier for primary biliary cirrhosis, presented with persistent fever and vomiting three months before admission. She had a history of pulmonary MAC diagnosed five years earlier but remained untreated due to stable lung lesions. Abdominal computed tomography (CT) during her current illness revealed new thickening at the jejuno-jejunal anastomosis site and enlarged mesenteric lymph nodes. Positron emission tomography-CT indicated increased uptake at these sites, suggesting a possible malignancy. Endoscopy revealed an elevated lesion with circumferential ulcers, leading to a suspicion of primary malignant lymphoma. However, biopsies showed CD68-positive histiocyte-like cells with numerous acid-fast bacilli, confirming disseminated MAC infection. Despite ongoing antimicrobial therapy, the patient’s intestinal lesions persisted, and she required prolonged hospitalization and interventions for bile drainage and enteral nutrition. Conclusion This case underscores the importance of considering disseminated MAC as a potential complication in solid organ transplant recipients, even when a long period has passed since transplantation. Disseminated MAC can mimic malignancy, presenting with significant lesions causing intestinal obstruction. Awareness and thorough differential diagnosis are essential for timely and accurate management in such complex cases. The patient’s outcome emphasizes the need for vigilance in managing long-term immunosuppressed patients, particularly when they present with atypical infections.